Multi-temporal analysis of land use change in the municipality of linares, Nuevo León - Hernández- Cavazos, María Cecilia; Sandoval-García, Rufino; Molina-Guerra, Víctor M.; Alanís-Rodríguez, Eduardo (Ecosistemas y Recursos Agropecuarios, 2023)
The aim of this research was to perform a multi-temporal analysis of land use change and vegetation cover in Linares, Nuevo León, México, at five different time periods: 1995-2008, 2008-2014, 2014-2021 and 1995-2021. For the analysis, a supervised classification of orthophotos and high-resolution satellite images GeoEye-1 and Birdseye was performed. The accuracy of the image classification presented average values of Kappa index of 0.76, considered within a substantial level of accuracy. With the data obtained, the annual deforestation rate was calculated using the equation proposed by Puyravaud. The results indicate that in a period of 26 years the municipality lost 61.77% of its oak-pine, pine-oak and oak forests, showing annual deforestation rates of -5.82%, -3.31% and -3.06% respectively; Likewise, 27.58% of submontane scrubland and 4.8% of rosetophilous desert scrubland were lost, with annual deforestation rates of -1.24 and -0.19%, respectively. Unlike the low deciduous spiny forest and the grassland, which showed an increase in plant cover of 310.58 and 18.09%, with annual exchange rates of 5.43 and 0.64%, respectively. These changes in land cover and use can affect global atmospheric and climate processes, so this study aims to serve as a reference for the design of public policies and programs for conservation and sustainable management of natural resources.
Keywords: Vegetation cover, satellite images, supervised classification, deforestation rate, human activities